Effects of Potentially Inappropriate Medications in Older Patients with Gastrointestinal System Cancer - Melike OZKAN; Irfan KARAHAN; Selim YALCIN; Gozde SENGUL AYCICEK (Medeniyet Medical Journal)
Objective: Potentially inappropriate medications (PIM) is a crucial problem in the geriatric population. The amount of prescription and unadherence increase because of the different problems encountered in cancer patients. Our aim was to evaluate the effects of PIM in patients with gastrointestinal system cancer and to investigate its relationship with chemotherapy side effects, mortality, and progression. Methods: This retrospective cohort study assessed 154 patients with gastrointestinal system cancer. Demographics and disease features, the presence of PIM according to the 'TIME-to-STOP' criteria and baseline laboratory parameters were recorded. The effects of PIM on survival and adverse treatment events were evaluated. Results: 66.9% of the cases were male and 33.1% were female. The mean age was 71.9+-6.4 years. The most common side effects of chemotherapy are nausea, vomiting, kidney injury, and pain. The most frequently used prescriptions among the 98 PIMs were gliclazide, hyoscine N-butylbromide, simethicone, diphenoxylate atropine, and thiocolchicoside. PIM was detected in 68.1% of the participants. Chemotherapy side effects were more common in PIM group (p<0.001, odds ratio =5.6). PIM had no effect on mortality. Factors associated with mortality were age, stage, albumin, creatinine, operation history, and progression. A significant relationship was found between age, cancer stage, albumin, creatinine, operation history, and PIM in the regression model. There was no relationship between PIM and progression-free survival. Conclusion: Chemotherapy toxicity may increase with PIM detected on diagnosis. We suggest that PIM is an important factor in predicting the side effects of chemotherapy and minimizing the adverse effects.